2020
DOI: 10.3389/fmicb.2020.599205
|View full text |Cite
|
Sign up to set email alerts
|

Brucella abortus BspJ Is a Nucleomodulin That Inhibits Macrophage Apoptosis and Promotes Intracellular Survival of Brucella

Abstract: To date, a variety of Brucella effector proteins have been found to mediate host cell secretion, autophagy, inflammation, and other signal pathways, but nuclear effector proteins have not yet been reported. We identified the first Brucella nucleomodulin, BspJ, and we screened out the BspJ interaction host proteins NME/NM23 nucleoside diphosphate kinase 2 (NME2) and creatine kinase B (CKB) through yeast two-hybrid and co-immunoprecipitation assays. These proteins ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 60 publications
1
18
0
Order By: Relevance
“…Compared with the control group, the p-JNK and p-p53 protein levels in the 8 h group were significantly increased ( Figures 1C–E ). Because Brucella has been reported to inhibit apoptosis in macrophages ( Ahmed et al., 2016 ; Ma et al., 2020 ), we examined apoptosis in B. suis S2-infected HMC3 cells at different timepoints by flow cytometry ( Figure 1G ). Flow cytometric analysis indicated that compared with the control group, the apoptosis rate in HMC3 cells was reduced in the 2 h group but was increased in the 8 h group ( Figure 1F ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compared with the control group, the p-JNK and p-p53 protein levels in the 8 h group were significantly increased ( Figures 1C–E ). Because Brucella has been reported to inhibit apoptosis in macrophages ( Ahmed et al., 2016 ; Ma et al., 2020 ), we examined apoptosis in B. suis S2-infected HMC3 cells at different timepoints by flow cytometry ( Figure 1G ). Flow cytometric analysis indicated that compared with the control group, the apoptosis rate in HMC3 cells was reduced in the 2 h group but was increased in the 8 h group ( Figure 1F ).…”
Section: Resultsmentioning
confidence: 99%
“…Brucella is able to escape the killing action of professional phagocytes by replicating diffusely within the endoplasmic reticulum of macrophages ( Ma et al., 2020 ). As a multifunctional protein in the endoplasmic reticulum, CALR plays a role in anti-apoptosis through regulating calcium ion concentration ( Gold et al., 2010 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that lung resident macrophages provide a replicative niche for wt Brucella strains ( 42 ). Within alveolar macrophages, Brucella inhibits host cell apoptosis, evades immune surveillance which in turn makes more difficult for antigen processing and presentation ( 53 , 54 ). In addition, during pulmonary infection with wt Brucella , alveolar macrophages inhibit pulmonary DC activation.…”
Section: Discussionmentioning
confidence: 99%
“…After the target genes were optimized, we commissioned GENERAL BIOL (Anhui, China) to synthesize the sequences and constructed each tandem sequence (FC, GS, and FCGS) by ligation into the vector pET28a/pET32a (EMD Biosciences, Novagen, San Diego, CA, USA). The Phyre2 software program ( http://www.sbg.bio.ic.ac.uk/phyre2/html/page.cgi?id=index ) was used to predict the tertiary structures of the recombinant fusion proteins ( 26 ).…”
Section: Methodsmentioning
confidence: 99%